Joint scores in hemophilic arthropathy in children: Developing country perspectives - Guha, Aritra (Eur J Rheumatol, 2020)
OBJECTIVE: Hemophilia is a common X-linked recessive coagulopathy causing recurrent bleeding into the synovial joints and results in articular and periarticular abnormalities. To our knowledge, this is the first comprehensive study aimed at studying the clinico-radiological joint score evaluation in hemophilic arthropathy in children from a developing country and its possible impact on the quality of life. METHODS: In this hospital-based, prospective, descriptive study, all children presenting to the pediatric rheumatology clinic were studied. The joint physical examination was scored using the Hemophilia Joint Health Score 2.1 (HJHS 2.1). The patients were then subjected to imaging of the most affected joint using ultrasonography (USG) and magnetic resonance imaging (MRI). Detailed USG and MRI radiological evaluation was recorded in the predesigned proforma using the Hemophilia Early Arthropathy Detection with Ultra Sound (HEAD-US) score and MRI DENVER score. The physical quality of life as per Functional Independence Score in Hemophilia (FISH) was noted. The clinical, radiological, and functional scores were analyzed with an appropriate statistical measure. RESULTS: The mean age at presentation was 7.4 years (interquartile range 4.9–10), with the knee being the most common joint involved. All of the USG score, MRI score, and FISH score have a significant correlation (p<0.05), with the HJHS 2.1 score with correlation coefficients of 0.7086, −0.8916, and 0.8607, respectively. USG and MRI had a correlation coefficient of −0.7145 and −0.8326 with FISH, respectively. CONCLUSION: The degree of association between HJHS 2.1 score was found to be maximum with HEAD-US score, whereas a negative correlation was seen evaluating FISH score with both HEAD-US and MRI DENVER scores. Use of these scores, specifically HEAD-US score, will result in consistent assessment of hemophilic joints, optimizing the management of the destructive changes.